Remaja visioner: Mengenal investasi dan mengelola keuangan remaja di SMK TAMTAMA 2 Sidareja - Gawik Setiawan; Andhi Johan Suzana; Dian Safitri Pantja Koesoemasari (Penamas: Journal of Community Service, 2026)
This community service program aimed to enhance students’ financial literacy and understanding of early investment at SMK Tamtama 2 Sidareja. The program was implemented using a participatory and contextual approach that comprised the stages of planning, implementation, and evaluation. The activities were conducted through material delivery, interactive discussions, and simple financial simulations. Program evaluation was conducted using pre- and post-test instruments to measure changes in participants’ understanding. The results indicated an average increase of 34% in students’ knowledge related to financial literacy concepts, pocket money management, and investment awareness. In addition to cognitive improvement, the program fostered students’ awareness of more rational financial behaviour, as reflected in their intentions to save and to control their consumption habits.